2002
DOI: 10.1103/physrevb.66.224415
|View full text |Cite
|
Sign up to set email alerts
|

55MnNMR investigation ofNd1x

Abstract: 55 Mn nuclear magnetic resonance ͑NMR͒ in Nd 1Ϫx Sr x MnO 3 (0.1рxр0.5) manganites provides local evidence of the magnetic inhomogeneities arising from the electronic structure changes below T C . The temperature dependences of magnetization, resistivity, and NMR spectra were compared in samples in the ferromagnetic insulating, ferromagnetic metallic, and charge-ordered phases. Spin-spin relaxation enhancement around 15 K is attributed to a critical slowing down of the Nd sublattice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The ground state of Nd 3+ ion (total moment J = 9/2, L = 6 and S = 3/2) is split by a low symmetric (lower than cubic) crystal field into the five doublets described by the effective spins S = 1/2. It is expected that a Mn-Nd exchange interactionĴ 12 is larger than that of the Nd-Nd [9,23]. We will show that the weak anisotropic couplingĴ 12 can give the needed contribution in Γ(τ ).…”
Section: Structural Datamentioning
confidence: 74%
See 1 more Smart Citation
“…The ground state of Nd 3+ ion (total moment J = 9/2, L = 6 and S = 3/2) is split by a low symmetric (lower than cubic) crystal field into the five doublets described by the effective spins S = 1/2. It is expected that a Mn-Nd exchange interactionĴ 12 is larger than that of the Nd-Nd [9,23]. We will show that the weak anisotropic couplingĴ 12 can give the needed contribution in Γ(τ ).…”
Section: Structural Datamentioning
confidence: 74%
“…In Nd 0.7 Ba 0.3 MnO 3 , the ordering of the Nd moments, that develops below 20 K [7], changed the magnetic and transport properties [8]. As study of the Nd 1−x Sr x MnO 3 (0.1 ≤ x ≤ 0.5) showed, the Nd magnetic subsystem came also into play at the low temperatures due to its ordering [9]. At the same time, no effects of the Mn-Nd coupling were found near T C in the investigations of critical static behavior of Nd 0.6 Pb 0.4 MnO 3 [10] and critical dynamics of Nd 1−x Sr x MnO 3 (x ≈ 0.5) [11].…”
Section: Introductionmentioning
confidence: 99%
“…A first possibility is the rare-earth magnetism of Pr and Nd, which might interact with the manganese spin network, as it has been proposed in some manganites [21,34]. Besides, it must be taken into account that although these concentrations (x = 0.4) are thought to be far from the charge-ordered antiferromagnetic phase with charge localization (x = 0.5) where phase segregation is well established [35], in some studies it was found that Nd 1−x Sr x MnO 3 (x = 0.3,0.4) also presented a weaker mechanism of carrier localization as well as phase segregation [36][37][38]. In other papers for x = 0.3, a competition between the double exchange mechanism and correlations arising from coupled spin and lattices degrees of freedom was found [24,37].…”
Section: Discussionmentioning
confidence: 99%
“…The shape of spectrum in the field of 1 T clearly differs from that taken in zero field, which suggests that applying the field removes the pinning of domain walls. The multi-peak spectra have also been observed for ferromagnetic metallic Nd 1Àx Sr x MnO 3 compounds [7].…”
mentioning
confidence: 87%